Challenges related to data protection in clinical research before and during the COVID-19 pandemic: An exploratory study - Lalova-Spinks, Teodora; De Sutter, Evelien; Valcke, Peggy; Kindt, Els; Lejeune, Stephane; Negrouk, Anastassia; Verhenneman, Griet; Derèze, Jean-Jacques; Storme, Ruth; Borry, Pascal; Meszaros, Janos; Huys, Isabelle (Frontiers in Medicine, 2022)
Background: The COVID-19 pandemic brought global disruption to health, society and economy, including to the conduct of clinical research. In the European Union (EU), the legal and ethical framework for research is complex and divergent. Many challenges exist in relation to the interplay of the various applicable rules, particularly with respect to compliance with the General Data Protection Regulation (GDPR). This study aimed to gain insights into the experience of key clinical research stakeholders (investigators, ethics committees (ECs), and data protection officers (DPOs)/legal experts working with clinical research sponsors) across the EU and the UK on the main challenges related to data protection in clinical research before and during the pandemic. Method: The study consisted of an online survey and follow-up semi-structured interviews. Data collection occurred between April and December 2021. Survey data was analyzed descriptively, and the interviews underwent a framework analysis. Results and conclusion: In total, 191 respondents filled in the survey, of whom fourteen participated in the follow-up interviews. Out of the targeted 28 countries (EU and UK), 25 were represented in the survey. The majority of stakeholders were based in Western Europe. This study empirically elucidated numerous key legal and ethical issues related to GDPR compliance in the context of (cross-border) clinical research. It showed that the lack of legal harmonization remains the biggest challenge in the field, and that it is present not only at the level of the interplay of key EU legislative acts and national implementation of the GDPR, but also when it comes to interpretation at local, regional and institutional levels. Moreover, the role of ECs in data protection was further explored and possible ways forward for its normative delineation were discussed. According to the participants, the pandemic did not bring additional legal challenges. Although practical challenges (for instance, mainly related to the provision of information to patients) were high due to the globally enacted crisis measures, the key problematic issues on (cross-border) health research, interpretations of the legal texts and compliance strategies remained largely the same.